Debonding Behavior of Conventional Concrete Strengthened with Anchored FRP and Staked - Ariyansyah, Rona; Gunadi, Riawan (Semarang State University, 2019)
Concrete structures can be damaged or deteriorate due to various reasons such as errors in planning, implementation factors, getting overload burden, decreased capacity and quality of structures, and changes in structural functions. Thus, to strengthen the damaged structures, there is a need for an investigation regarding the damage to the existing concrete structures. Retrofitting FRP (Fiber Reinforced Polymer) to the damaged structures can be a reinforcement alternative. The bond shear between FRP and concrete need to be considered in using FRP to solve the damaged structure. Shear behavior on the bonded structures greatly affects the condition of the structure. Therefore, this study aimed to examine the effect of anchors and stakes on FRP debonding behavior. This study was carried out experimentally to obtain the results and data on the effects of the anchors and stakes. This study used 9 specimens with a size of 150 mm x 150 mm x 300 mm. From those 9 specimens, 3 specimens were specimens without reinforcement (FR), 3 specimens were reinforced with anchor (FRA), and 3 specimens were reinforced with anchor and stake (FRAP). The test method used in this study referred to ASTM D5379 concerning the Standard Test Method for Shear Properties of Composite Materials. From the bond shear test of each FR, FRA, and FRAP specimens, it was found that the average maximum shear load was 19.405 kN, 28.465 kN, and 29.699 kN, consecutively.